Propulsive power and blade efficiency - Kleshnev, V. (BioRow, 2021)
Using the three types of power (handle power, blade power and system power ), it is possible to derive the efficiencies of the power transformation processes as the ratios of their average values over the stroke cycle. This analysis has been applied to the recent data obtained in M1x using three different blade types: Smoothie, Comp and Fat2 (dimensions - in RBN 2020/11). Rowing speed and power (Fig.2, Tab.1) were the highest in the first run with Smooth blades; gross DF was very similar, confirming consistent weather conditions. The blade efficiency (Tab.2) defined with the slippage (RBN 2018/06) was the highest with Smooth, but these blades had the lowest ratio of the blade/handle powers, which could be related to a higher blade axial force in Smooth creating higher drag (Fig.2,a). The ratio of the system/blade powers was highest in the Comps (less axial force than in Smooth) and the lowest in Fat2, which could be explained by a shorter outboard - higher blade force - more slippage and the lowest efficiency of Fat2. As magnitudes of Eblade.slip and Esys/handle were quite similar, and it is still not clear which one is more important, their average values were taken as an overall efficiency. Based on this, the Comp blades were the most efficient with 79.5%, Fat2 were the second with 77.6% and Smooth - the last ones with 77.4%. With the above levels of rowing speed and power, Comp would be 3.4s faster over 2km than Fat2, and 3.9s faster than Smooth blades. Similar results were obtained at lower stroke rates 20, 25, 30spm. More detailed discussion will follow…